2022
DOI: 10.5194/nhess-22-775-2022
|View full text |Cite
|
Sign up to set email alerts
|

Compound flood modeling framework for surface–subsurface water interactions

Abstract: Abstract. Compound floods are an active area of research in which the complex interaction between pluvial, fluvial, coastal and groundwater flooding are analyzed. A number of studies have simulated the compound flooding impacts of precipitation, river discharge and storm surge variables with different numerical models and linking techniques. However, groundwater flooding is often neglected in flood risk assessments due to its sporadic frequency (as most regions have water tables sufficiently low that do not ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The evaluation, however, suggested that the Ribe Flood model was able to replicate the flooded areas in most instances. There is, however, a need for more data to validate flooding events like this, especially ground truth data as e.g., drone images (Iqbal et al, 2023), citizen science e.g, photos (Peña et al, 2022) and piezometers (Neri-Flores et al, 2019). Additionally, future modelling efforts assessing flooding may seek to include the impact of cascading events like dam breaks or sediment deposits in drainage systems, though it would require information on location and timing of such events, which may not be readily available.…”
Section: Hydraulic River Flow and Flood Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation, however, suggested that the Ribe Flood model was able to replicate the flooded areas in most instances. There is, however, a need for more data to validate flooding events like this, especially ground truth data as e.g., drone images (Iqbal et al, 2023), citizen science e.g, photos (Peña et al, 2022) and piezometers (Neri-Flores et al, 2019). Additionally, future modelling efforts assessing flooding may seek to include the impact of cascading events like dam breaks or sediment deposits in drainage systems, though it would require information on location and timing of such events, which may not be readily available.…”
Section: Hydraulic River Flow and Flood Modelmentioning
confidence: 99%
“…The study found that groundwater flooding was frequent on the floodplain. Peña et al (2022) simulated three flooding events with a coupled FLO-2D and MODFLOW model in Florida, USA. The events had high rainfall, water table and normal tide conditions to investigate the groundwater contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of process-based modeling is the ability to simulate complex WL dynamics such as backwater effects, tidal propagation, and overtopping in estuarine environments and urban settings that are usually ignored in point-based statistical analyses (Gallien et al, 2018;Kumbier et al, 2018;Leijnse et al, 2021). Also, processbased models can simulate complex CF dynamics in coastal to inland transition zones where hydrological and coastal processes determine flood extent, duration, and inundation depth (Bilskie et al, 2021;Jafarzadegan et al, 2023;Peña et al, 2022). Nevertheless, CF modeling is subject to uncertainties that interact and cascade in series throughout the modeling chain if they are not treated appropriately (Beven et al, 2005;Hasan Tanim and Goharian, 2021;Meresa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%